Front Cover: Fibrous Bundles in Biomorph Systems: Surface‐Specific Growth and Interaction with Microposts (ChemSystemsChem 4/2021). Issue 4 (10th June 2021) - Knoll, Pamela; D'Silva, Denvert S.; Adeoye, Damilola I.; Roper, Michael G.; Steinbock, Oliver
Abstract : The Front Cover shows a pseudo‐color representation of an optical micrograph illustrating two key findings: a new type of polycrystalline biomorph (cyan) and its ability to dislodge, push, and flip small resin disks (red/cyan). More information can be found in the Article by Oliver Steinbock and co‐workers .